METHODOLOGY OF TEACHING MATHEMATICS IN RELATIONSHIP WITH OTHER SUBJECTS - Masharipova Muyassar Shomurodovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article discusses different perspectives, methods, and contributors to the teaching of mathematics, interesting topics, and the interrelationships of mathematics with other disciplines, as well as the attitudes of scholars who have contributed to it.